Exploring the occurrence of Listeria in biofilms and deciphering the bacterial community in a frozen vegetable producing environment - Pracser, Nadja; Voglauer, Eva M.; Thalguter, Sarah; Pietzka, Ariane; Selberherr, Evelyne; Wagner, Martin; Rychli, Kathrin (Frontiers in Microbiology, 2024)
The establishment of Listeria (L.) monocytogenes within food processing environments constitutes a significant public health concern. This versatile bacterium demonstrates an exceptional capacity to endure challenging environmental conditions in the food processing environment, where contamination of food products regularly occurs. The diverse repertoire of stress resistance genes, the potential to colonize biofilms, and the support of a co-existing microbiota have been proposed as root causes for the survival of L. monocytogenes in food processing environments. In this study, 71 sites were sampled after cleaning and disinfection in a European frozen vegetable processing facility, where L. monocytogenes in-house clones persisted for years. L. monocytogenes and L. innocua were detected by a culture-dependent method at 14 sampling sites, mainly conveyor belts and associated parts. The presence of biofilms, as determined by the quantification of bacterial load and the analysis of extracellular matrix components (carbohydrates, proteins, extracellular DNA) was confirmed at nine sites (12.7%). In two cases, L. innocua was detected in a biofilm. Furthermore, we explored the resident microbial community in the processing environment and on biofilm-positive sites, as well as the co-occurrence of bacterial taxa with Listeria by 16S rRNA gene sequencing. Pseudomonas, Acinetobacter and Exiguobacterium dominated the microbial community of the processing environment. Using differential abundance analysis, amplicon sequence variants (ASVs) assigned to Enterobacterales (Enterobacter, Serratia, unclassified Enterobacteriaceae) and Carnobacterium were found to be significantly higher abundant in Listeria-positive samples. Several Pseudomonas ASVs were less abundant in Listeria-positive compared to Listeria-negative samples. Acinetobacter, Pseudomonas, Janthinobacterium, Brevundimonas, and Exiguobacterium were key players in the microbial community in biofilms, and Exiguobacterium and Janthinobacterium were more abundant in biofilms. Further, the microbial composition varied between the different areas and the surface materials.